Simulation of the migration of dissolved contaminants through a subaqueous capping layer: model development and application for As migration. Issue 3 (1st May 2003) - Dueri, Sibylle; Therrien, René; Locat, Jacques
Abstract : TRANSCAP-1D is a numerical model that simulates the vertical migration of dissolved contaminants through a subaqueous capping layer. The model was developed for the prediction of the long-term effectiveness of a sediment cap. It considers advection, diffusion, chemical reactions, and the effect of the burrowing activity of the benthic fauna. The sediment is represented as a dual porosity medium composed of sediment pores and biologically formed tubes. The numerical model was calibrated with the concentration profiles of dissolved arsenic measured in the sediments at two sampling stations in the Saguenay Fjord, in Québec, Canada, where a major flood event caused the natural capping of contaminated sediments. Thereafter several numerical simulations with variable bio-irrigation depth and variable thickness of the capping layer were performed to test the effect of the uncertainty and variability of the input values on the model response. These simulations indicate that the depth of bio-irrigation in the sediment and the release from mineral dissolution are major factors controlling the distribution of dissolved contaminants in the sediment column. Key words: Saguenay Fjord, migration, numerical model, capping layer, sediment, bio-irrigation, heavy metals, arsenic.